2015
DOI: 10.1097/bot.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cost of Negative Pressure Dressings Is Not Justified for Split-Thickness Skin Grafting of Low-Risk Wounds

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Another similar retrospective study performed by Kempton et al showed no significant difference between NPWT and CBD in the success of STSG take, and based on this data and a cost analysis concluded that NPWT is not a viable alternative to CBD; however, the patients included in this study were treated only for low risk wounds with a low STSG failure rate, and the cost analysis did not account for the monetary expense of an extended stay in the hospital needed for CBD. 9 From our analysis, NPWT has a significant benefit over CBD, reducing risk of STSG failure in a wide range of wound types and sizes, and thus has both the statistical and clinical significance necessary to be deemed appropriate to use in the case of most wounds over bolster dressing. A prospective, randomized study on the effect of NPWT versus CBD on wounds with varying levels of acuity from low to high risk of STSG failure could be helpful in determining a distinct guideline for when it is most appropriate to use NPWT.…”
Section: Discussion Npwtmentioning
confidence: 91%
“…Another similar retrospective study performed by Kempton et al showed no significant difference between NPWT and CBD in the success of STSG take, and based on this data and a cost analysis concluded that NPWT is not a viable alternative to CBD; however, the patients included in this study were treated only for low risk wounds with a low STSG failure rate, and the cost analysis did not account for the monetary expense of an extended stay in the hospital needed for CBD. 9 From our analysis, NPWT has a significant benefit over CBD, reducing risk of STSG failure in a wide range of wound types and sizes, and thus has both the statistical and clinical significance necessary to be deemed appropriate to use in the case of most wounds over bolster dressing. A prospective, randomized study on the effect of NPWT versus CBD on wounds with varying levels of acuity from low to high risk of STSG failure could be helpful in determining a distinct guideline for when it is most appropriate to use NPWT.…”
Section: Discussion Npwtmentioning
confidence: 91%
“…27,28 However, Kempton et al examined differences in cost and outcomes between NPC and conventional compressive dressings for STSG stabilization of traumatic extremity wounds, which were regarded as low risk defects for skin graft loss, and demonstrated that the mean cost associated with NPC was significantly higher than that of conventional compressive dressings whereas the outcomes of NPC for skin grafts were not superior to those of conventional compressive dressings. 26 Therefore, given the expense, we suggest that NPC for skin graft stabilization should be applied only for high risk defects of skin graft loss, such as large or muscle-exposing defects as conducted in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Although favorable results were obtained in this study, the cost of NPC is generally high. 26 The high cost of NPC, however, might be offset by the benefits of improved skin graft survival and reduced complications. 27,28 However, Kempton et al examined differences in cost and outcomes between NPC and conventional compressive dressings for STSG stabilization of traumatic extremity wounds, which were regarded as low risk defects for skin graft loss, and demonstrated that the mean cost associated with NPC was significantly higher than that of conventional compressive dressings whereas the outcomes of NPC for skin grafts were not superior to those of conventional compressive dressings.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, and importantly, in low-risk wounds, the price associated with VAC may not be justified, and in this setting simpler methods of compression are better indicated (20). The argument of using compression over NPWT from a cost effectiveness standpoint was also supported in one study for the closure of radial forearm donor sites (21).…”
Section: Discussionmentioning
confidence: 99%